Serum CA 125 level in normotensive and pre-eclamptic pregnancies in a tertiary care hospital - Sivaprasad, Sahithya; S. R., Sheela; Nagaraj, Shashidhar Kurpad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preeclampsia is one main reason for high-risk pregnancy. Among the disorders in hypertension, preeclampsia develops in antenatal period and it is defined by high blood pressure of more than 140/90 mmHg and arteriolar vasoconstriction, both of which lower uteroplacental perfusion and ultimately lead to placental hypoxia. The objectives of this study was (a) to estimate CA125 level in normotensive and pre eclamptic pregnancies; and (b) to predict severity of pre-eclampsia with CA125 levels with cut off value of CA125 level as 23.7 IU/ml. Methods: This two year cross sectional study was conducted on all antenatal mothers bestween 20 -40 weeks gestational age getting admitted RLJH and research centre Tamaka (January 2021-December 2022), for the period of 2 years who fulfilled inclusion and exclusion criteria. Detailed clinical history along with antenatal examination was done. For each study subject the blood pressure was recorded. Complete blood picture was done and CA125 levels were done of the study subjects. Results: Mean CA125 among normal subjects was 24.24±13.71 IU/ml and Mean CA125 among pre-eclampsia subjects was 30.61±15.69 IU/ml. There was a statistical significance found between two groups with respect to CA125. Conclusions: In pre-eclampsia, CA125 was increased more compared to normotensive group. This indicates the importance in estimation of CA125 level in preeclampsia. The same has been determined with significant p value.